2008
DOI: 10.1073/pnas.0810199105
|View full text |Cite
|
Sign up to set email alerts
|

Myc regulates a transcriptional program that stimulates mitochondrial glutaminolysis and leads to glutamine addiction

Abstract: Mammalian cells fuel their growth and proliferation through the catabolism of two main substrates: glucose and glutamine. Most of the remaining metabolites taken up by proliferating cells are not catabolized, but instead are used as building blocks during anabolic macromolecular synthesis. Investigations of phosphoinositol 3-kinase (PI3K) and its downstream effector AKT have confirmed that these oncogenes play a direct role in stimulating glucose uptake and metabolism, rendering the transformed cell addicted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
1,761
5
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,750 publications
(1,844 citation statements)
references
References 33 publications
61
1,761
5
17
Order By: Relevance
“…Adherent cell lines 293T (purchased from ATCC) and SFXL (SF188 cells with stable expression of Bcl-XL; generated as previously described 51 ) were maintained at low passage number in high glucose DMEM with 10% FBS, glucose 25 mM, glutamine 4 mM, penicillin 100 units/ml, and streptomycin 100 μg/ml and split every 2–3 days before reaching confluence. Cell lines were authenticated by Short Tandem Repeat (STR) profiling.…”
Section: Methodsmentioning
confidence: 99%
“…Adherent cell lines 293T (purchased from ATCC) and SFXL (SF188 cells with stable expression of Bcl-XL; generated as previously described 51 ) were maintained at low passage number in high glucose DMEM with 10% FBS, glucose 25 mM, glutamine 4 mM, penicillin 100 units/ml, and streptomycin 100 μg/ml and split every 2–3 days before reaching confluence. Cell lines were authenticated by Short Tandem Repeat (STR) profiling.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent experiments showed that Myc-transformed cells, when challenged with an inhibitor of glutamate-dependent transaminases [known as aminooxyacetate (AOA)], activated the intrinsic apoptotic pathway as the mechanism of cell death. Interestingly, when Myc-transformed cells were supplemented with cell-permeable α-KG, these cells increased sensitivity to resist apoptosis [14]. Other studies have shown that Myc regulates glutamine metabolism in human cancer cells by transcriptionally repressing microRNAs: known as miR23a/b.…”
Section: Mycmentioning
confidence: 99%
“…The metabolic state is primarily based on nutrients available to the tumors which have rewired their metabolic pathways, thereby contributing to this metabolic autonomy [5][6][7][8]. The discoveries of oncogenes and tumor suppressors that regulate nutrient uptake and its utilization have provided insights that nutrients per se play a pivotal role in cell growth and proliferation through a wide array of cell signaling pathways [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Myc promotes the expression of the glutamine transporters ASCT2 and SN2, and the mitochondrial enzyme glutaminase, which converts glutamine to glutamate (Wise et al, 2008;Gao et al, 2009). These events cause cells transformed with Myc to be dependent on glutamine for survival (Yuneva et al, 2007).…”
Section: Effects Of Metabolic Reprogramming On Autophagy: Glutaminolysismentioning
confidence: 99%